Isolation and study of the optimum growth conditions of diesel degrading bacteria from soil - Naila, Tasmin (BRAC University, 2015)
This thesis report is submitted in partial fulfillment of the requirement for the degree of Bachelor of Science in Biotechnology, 2015.